Private Health Insurance Exchanges Early Evidence and Implications for the Future - Buttorff, Christine (RAND Corporation, 2016)
Private exchanges offer employer health insurance, combining online shopping, increased plan choice, benefit administration, and cost-containment strategies. This report examines how private exchanges function, how they may affect employers and employees, and the possible implications for the Affordable Care Act's Small Business Health Options Program Marketplaces.